Analysis of the signal measured in spectral-domain optical coherence tomography based on nonlinear interferometers - Rojas-Santana, Arturo; Machado, Gerard J.; Chekhova, Maria; Lopez-Mago, Dorilian; Torres, Juan P. (Physical Review A, 2022)
We analyze and compare the output signals obtained in three different configurations of optical coherence tomography (OCT). After appropriate processing, these signals are used to retrieve an image of the sample under investigation. One of the configurations considered is the common choice in most OCT applications and is based on the use of a Michelson interferometer. For brevity, here we refer to it as standard OCT. The other two configurations are two types of optical coherence tomography based on the use of so-called nonlinear interferometers, interferometers that contain optical parametric amplifiers inside. The goal is to highlight the differences and similarities between the output signals measured in standard OCT and in these two OCT schemes, with the aim of evaluating if retrieval of information about the sample can be better done in one case over the others. We consider schemes where the optical sectioning of the sample is obtained by measuring the output signal spectrum (spectral or Fourier-domain OCT), since it shows better performance in terms of speed and sensitivity than the counterpart time-domain OCT.
CRIS-Team Scopus Importer:2022-09-30